Manajemen Implementasi Nilai-nilai Moderasi Beragama pada Pondok Pesantren dan Sekolah di Kabupaten Tanah Datar - Lita Sari Muchlis; Abhanda Amra; Demina Demina; Saputra Habci Amran; Elisnia Rezika; Iman Asroa B.S (ISLAMIKA, 2023)
This research aims to describe the implementation management of religious moderation values at the Thawalib Tanjung Limau Islamic boarding school and SMPN 1 Batusangkar. The widespread implementation and implementation of religious moderation as well as the internalization of the values of religious moderation in the world of education are the background for this research. The research was carried out using a qualitative approach with the type of field research. The data in this research were obtained from interviews and observations with school leaders or principals and teachers at the Thawalib Tanjung Limau Islamic boarding school and SMPN 1 Batusangkar. The research results show that these two educational institutions are quite good at managing the implementation of religious moderation values. This is proven by the stages carried out to implement the values of religious moderation in the two educational institutions. Implementing the values of religious moderation in management starts from planning, implementation, strategies used, as well as analyzing obstacles and offering solutions to solve them so that the program runs well. In fact, it appears that there are no cases of discrimination and intolerance due to religious differences. However, the results of this research also show that the name religious moderation is still something new, so there are still many teachers who do not understand the meaning of religious moderation.